Assessing the Factor Influence on Patent Activity in Mining and Metallurgical Industry (e.g. Nano Products) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The creation of an intellectual property product with a vector of effective implementation into production predetermines the search for optimal proportions of interaction between scientific, industrial, and educational parameters. Scientific, industrial and educational types of organizations are proposed to be interpreted as objects of interrelated elements that have a direct impact on patent activity in the field of nano production. Additional emphasis was placed on the factors that arise in the process of commercialization of objects of intellectual activity and have a critical impact on the final results of the process. In this connection, it was proposed to introduce the concept of dysfunction (a dysfunctional indicator of the promotion of high technology products), considered as a factor-obstacle in the process of entering the market of intellectual property. It also introduces the definition of success (an indicator of the success of promoting science-intensive products), considered as a vector antonym of dysfunction, which is a defining tool to improve the effectiveness of the strategy for the commercialization of scientific developments and projects.The paper defines the boundaries of the indicators of success and the dysfunctionality of the patent activity of high technology products using the example of nanomaterials. The indicators were evaluated for their compliance with the proposed criteria. This approach can be positioned as a way to identify and correct dysfunctional and successful factors that predetermine the effectiveness of patent activity of high technology products in the mining and metallurgical industry.The article proposes a model for assessing the factors affecting patent activity in the mining and metallurgical complex, based on the division of factors into blocks of standard and specific purposes, based on the specifics of the nano object of the mining and metallurgical complex as a product on the market. The model includes scientific, educational, and industrial indices that have a direct impact on patenting activity in the field of nanomaterials and nanotechnology in the mining and metallurgical industry. The correspondence of scientific, production, and educational parameters was checked on the example of a science-intensive product of the proposed model for increasing patent activity